2008
DOI: 10.1161/hypertensionaha.107.100594
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance in Sex Hormone Levels Exacerbates Diabetic Renal Disease

Abstract: Abstract-Studies suggest that the presence of testosterone exacerbates, whereas the absence of testosterone attenuates, the development of nondiabetic renal disease. However, the effects of the absence of testosterone in diabetic renal disease have not been studied. The study was performed in male Sprague-Dawley nondiabetic, streptozotocin-induced diabetic, and streptozotocin-induced castrated rats (nϭ10 to 11 per group) for 14 weeks. Diabetes was associated with the following increases: 3.2-fold in urine albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
65
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 36 publications
9
65
0
2
Order By: Relevance
“…Several experimental studies have demonstrated a renoprotective role of exogenous oestrogens in models of type 1 diabetic retinopathy and nephropathy [36][37][38][39]. However, an experimental model of type 1 diabetes has also, however, shown that relative balance, rather than the absolute levels of sex hormones, correlates with conditions associated with diabetic complications [40].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have demonstrated a renoprotective role of exogenous oestrogens in models of type 1 diabetic retinopathy and nephropathy [36][37][38][39]. However, an experimental model of type 1 diabetes has also, however, shown that relative balance, rather than the absolute levels of sex hormones, correlates with conditions associated with diabetic complications [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, removal of the anabolic effects of testosterone in the setting of the wasting syndrome of uncontrolled diabetes may contribute to further deterioration of renal function. Also, expression of profibrotic molecules, such as transforming growth factor-␤ and matrix degradation enzymes, may be differentially controlled by sex hormones, 15 which may explain the effect of castration on these parameters as found by Xu et al 10 In summary, one thing is certain: sex matters. The study of Xu et al, 10 far from exhausting the possible explanations, opens new avenues for research into the role of sex hormones in altering the course of diabetic nephropathy.…”
mentioning
confidence: 87%
“…Also, expression of profibrotic molecules, such as transforming growth factor-␤ and matrix degradation enzymes, may be differentially controlled by sex hormones, 15 which may explain the effect of castration on these parameters as found by Xu et al 10 In summary, one thing is certain: sex matters. The study of Xu et al, 10 far from exhausting the possible explanations, opens new avenues for research into the role of sex hormones in altering the course of diabetic nephropathy. As conventional paradigms fail to encompass the wealth of contemporary experimental evidence, clinical practice would certainly benefit from a thorough understanding of the mechanisms underlying the effects of sex hormones on the kidney and cardiovascular system.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…У роботі Qin Xu та співавт. було продемонстровано, що діабет і гіперглікемія асоційовані зі зниженням плазмового рівня тестостерону й підвищенням плазмового рівня естрадіолу [8]. Також наявні дані щодо зв'язку між збільшенням рівня естрогенів і зменшенням чутливості клітин до інсуліну.…”
unclassified